Investor herd behaviour in Africa's emerging and frontier markets - Aawaar, Godfred; Boamah, Nicholas Addai; Akotey, Joseph Oscar (International Journal of Economics and Financial Issues, 2020)
Daily returns of 224 stocks traded on three distinctively classified markets (stand-alone, frontier, and emerging) within a developing continent context are used, employing the Chang, Chen and Khorana (2000) measure. We provide evidence of the presence of investor herding in Africa's emerging and frontier markets. Evidence of asymmetric herding activities during various market conditions is further provided. The paper also shows that the 2007-2009 global financial crisis did not intensify herding in African markets. The findings suggest that Africa's leading markets are still fairly inefficient, allowing for potential excess returns for investment strategies that seek to explore market anomalies. Keywords: Behavioural finance, Investor behaviour, Herding, African markets, Asymmetric herding. JEL Classifications: G01, G10, G14, G15 DOI: https://doi.org/10.32479/ijefi.10709